Numerical Simulation of Damage in Sandwich Composite Panels Due to Hydrodynamic Impact - Satrio Wicaksono; Nur Ridhwan Muharram; Hermawan Judawisastra; Tatacipta Dirgantara (Journal of Engineering and Technological Sciences, 2021)
The float and hull are vital parts of amphibious planes and boats, respectively, as both have to absorb hydrodynamic impact due to interaction with water. Sandwich composite panels are commonly used for such applications and other impact-absorbing structures. Unfortunately, the failure mechanism of sandwich composite panels under hydrodynamic impact is very complicated, as it may consist of composite skin failure, core failure, and non-uniform delamination. Hence, a numerical study on the damage of sandwich composite panels under hydrodynamic load is necessary. In this study, numerical simulation implementing the Coupled Eulerian-Lagrangian (CEL) method was performed to observe the damage mechanism of sandwich composite panels. The CEL method combines the Lagrangian and Eulerian frames into one model. Thus, analysis of structure deformation and fluid motion can be performed simultaneously. The result of the current numerical simulation shows a fair agreement with the experimental results in the literature, which shows that the current methodology can represent the sandwich composite panel response in real-life conditions, especially before shear core failure initiates.